Laser-Induced Shockwave (LIS) to Study Neuronal Ca2+ Responses - Gomez Godinez, Veronica; Morar, Vikash; Carmona, Christopher; Gu, Yingli; Sung, Kijung; Shi, Linda Z.; Wu, Chengbiao; Preece, Daryl; Berns, Michael W. (Frontiers in Bioengineering and Biotechnology, 2021)
Laser-induced shockwaves (LIS) can be utilized as a method to subject cells to conditions similar to those occurring during a blast-induced traumatic brain injury. The pairing of LIS with genetically encoded biosensors allows researchers to monitor the immediate molecular events resulting from such an injury. In this study, we utilized the genetically encoded Ca2+ FRET biosensor D3CPV to study the immediate Ca2+ response to laser-induced shockwave in cortical neurons and Schwann cells. Our results show that both cell types exhibit a transient Ca2+ increase irrespective of extracellular Ca2+ conditions. LIS allows for the simultaneous monitoring of the effects of shear stress on cells, as well as nearby cell damage and death.